Respuesta :

(2x + 8)(4x + 7) = 2x(4x + 7) + 8(4x + 7) = 8x^2 + 14x + 32x + 56 =
8x^2 + 46x + 56 <==

Answer:

B. [tex]8x^2+46x+56[/tex]

Step-by-step explanation:

We must multiply the elements of each parenthesis by the terms of the other parenthesis, We will have the following:

[tex](2x + 8)(4x + 7)=(2x)(4x)+(2x)(7)+(8)(4x)+(8)(7)\\(2x + 8)(4x + 7)=8x^2+14x+32x+56\\[/tex]

We have two terms with x, so we add them:

[tex](2x + 8)(4x + 7)=8x^2+46x+56[/tex]

So the correct answer is B.

ACCESS MORE